2023
DOI: 10.3390/atmos14030517
|View full text |Cite
|
Sign up to set email alerts
|

Global Navigation Satellite System-Based Retrieval of Precipitable Water Vapor and Its Relationship with Rainfall and Drought in Qinghai, China

Abstract: Qinghai Province is situated deep in inland China, on the Qinghai-Tibet plateau, and it has unique climate change characteristics. Therefore, understanding the temporal and spatial distributions of water vapor in this region can be of great significance. The present study applied global navigation satellite system (GNSS) technology to retrieve precipitable water vapor (PWV) in Qinghai and analyzed its relationship with rainfall and drought. Firstly, radiosonde (RS) data is used to verify the precision of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The rain was mainly located on the northwest side of the typhoon center, and with the incre (decrease) in intensity, the absolute value of vertical helicity on the west side of the phoon center increased (decreases), to some extent, which promoted (hinders) the dev opment of ascending motion in the region, resulting in more (less) water-vapor cond sation and rain. Therefore, regarding Figures 2 and 5, the rainfall caused by typho transit was less, or there was no rainfall, with a weakening typhoon intensity [11].…”
Section: Station Num-mentioning
confidence: 94%
See 1 more Smart Citation
“…The rain was mainly located on the northwest side of the typhoon center, and with the incre (decrease) in intensity, the absolute value of vertical helicity on the west side of the phoon center increased (decreases), to some extent, which promoted (hinders) the dev opment of ascending motion in the region, resulting in more (less) water-vapor cond sation and rain. Therefore, regarding Figures 2 and 5, the rainfall caused by typho transit was less, or there was no rainfall, with a weakening typhoon intensity [11].…”
Section: Station Num-mentioning
confidence: 94%
“…Among them, ECMWF provides the latest global atmospheric numerical forecast reanalysis data and forecast data for users, which is adopted in a lot of research by many institutions and scholars at home and abroad. Using RMSE, ME and other indicators, researchers evaluated the PWV estimation value inverted by the latest generation of MERRA-2 and ERA5 NWP data [9][10][11], and finally found that the PWV estimation value inverted by ERA5 is more accurate.…”
Section: Introductionmentioning
confidence: 99%